The Effect of Zephyr Layer Orientation on Zephyrboard Made from Oil Palm Petiole - Wardani, Lusita; Massijaya, Muhamad Yusram; Hadi, Yusuf Sudo; Darmawan, I Wayan (UI Scholars Hub, 2014)
It is very important to utilize oil palm petiole for the production of zephyr boards. This study aimed to analyze the effect of layer orientation on zephyr board quality. Zephyr boards were made with three coating patterns (A = cross perpendicular, B= combine A and C, and C= paralell) and five zephyr layers using urea formaldehyde adhesive. They were pressed for 20 min at a pressure of 25 kgf/cm² and a temperature 120 ºC, to a target density of 0.80 g/cm³ and a size of 300 mm X 300 mm X 12 mm. Our results showed that the physical and mechanical properties fulfilled the standards of JIS A 5908-2003. The best physical properties were found in the type C layer pattern, which had a density of 0.82 g/cm³, Mouisture Content of 9.46%, Water Absorpsion of 16.49%, and Thickness Swelling of 16.49%. The best mechanical properties—Modulus Of Elasticity and Modulus Of Repture —were also found in the type C layer pattern, with values of 35.2 x 10-3 kgf/cm² and 603.9 kgf/cm², respectively. However, the best IB and screw holding strength (SW) results were found with the type B layer pattern (Internal bonding B of 38.65 kgf/cm², Screw Withdrawl of 145.11 kgf).